M. Rudenko versus K. Marx: the Ukrainian Exposure of the Senselessness of the Economic Component of Marxism - Shevchuk, V. O. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
Evidences denying the argument about humanistic stances of K. Marx are given, and the falseness of the economic component of Marxism and its ideological system as a whole are shown. It is demonstrated that the knowledge enabling the denial of the Marxist verdict to “reactionary classes” and “reactionary nations” takes the roots in the Ukrainian academic community. The essential points of the critique of Marx’s “Capital” by Ukrainian scientist M. Rudenko are given. According to M. Rudenko, Marxist “achievements”, if looked at closely, turn to be but dissected theses of English political economy. The falseness of Marx’s doctrines is in making absolute what is in fact relative. From the A. Smith’s theory he extracts but two elements: the labor, made absolute and put above the nature, with the invented “social substance” as the source for additional value, and the clear-cut break of the society into classes. Rudenko, as a representative of the academic school of physical economy, offers his own conceptual model of capital by breaking it into absolute and relative one, and showing that the latter derives only from the former. He demonstrates that capital is a value capable of generating an additional value. The categories of capital that he shows can, accordingly, generate an absolute additional value and a relative additional value. In this way, a radically distinct concept of capital and capitalism appears. It is stressed that the European physiocracy, the Ukrainian academic school of physical economy and the modern physics-economics thought constitutes the fundamental part of the economic knowledge base of the humanity, whereas the political economy (with the Marxist economic component included) has derivative or secondary role.